Biofilms within the human body and its clinical implications - Jordão, Luísa (2018)
Biofilms with medical implications could be find on medical devices or on organs. Here we discuss the results obtained in two studies one associated with an organ (adenoid) and another associated with a medical device (central venous catheters- CVC). In the first study, we evaluate the association between biofilm assembly on adenoids and the incidence of recurrent infections in a paediatric population comparing adenoid samples from adenoidectomy groups with and without infectious indication. Biofilms were present in 27.4% of the adenoid samples. For H. influenzae, S. aureus, S. pyogenes, S. pneumococcus and M. catarrhalis, no association was found between ability to assemble biofilms in vitro and the presence of biofilms on adenoids, and the same was found for antibiotic resistance. The most isolated bacterium was H. influenzae that revealed after further characterization to be non-typeable (NT). No statistical difference was found on biofilm presence between the two groups, infectious versus non-infectious diagnosis. The same was true for biofilm assembling ability of bacteria found on adenoid surface and core. As in other studies, we did not find a correlation between biofilm formation and susceptibility or resistance to antibiotics and this raise the question of the importance of biofilms on the pathogenesis of infectious diseases. In the second study, we explore the relation between the presence of biofilms on central venous catheters and central venous catheter-related bloodstream infection (CRBSI). Our preliminary results (relative to data collected over 10 months) show that Staphylococci, either coagulase negative or positive, are major etiologic agents of this healthcare associated infection.